STANDAR PENDIDIK DAN TENAGA KEPENDIDIKAN PADA JENJANG SD: STUDI KASUS PADA SD NEGERI 1 GADUNGAN - Surya Novalina Panjaitan; Dion Saputra; Amalia Imtihani; Ni Wayan Rati; I Wayan Lasmawan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the standards of educators and education personnel (PTK) at the elementary school level, using SDN 1 Gadungan, Tabanan Regency, Bali as a case study. The research employs a qualitative descriptive case study approach with document analysis and observation methods. The findings reveal that 100% of PTK hold a minimum S1 academic qualification, a teacher-student ratio of 1:10.75 (surpassing the national standard of 1:20), and a certification rate of 88.89%. However, there are identified challenges including uneven workload distribution across classes, limited subject teachers for several disciplines, absence of postgraduate-qualified teachers, and inadequate digital infrastructure. The study concludes that SDN 1 Gadungan has largely met the minimum national standards under Permendikdasmen No. 47/2023, yet requires strategic improvements in workload redistribution, digital competency development, and teacher certification completion to optimize educational quality in alignment with the Merdeka Curriculum demands.